Arterial spin labeling‐fast imaging with steady‐state free precession (ASL‐FISP): a rapid and quantitative perfusion technique for high‐field MRI. (3rd June 2014) - Gao, Ying; Goodnough, Candida L.; Erokwu, Bernadette O.; Farr, George W.; Darrah, Rebecca; Lu, Lan; Dell, Katherine M.; Yu, Xin; Flask, Chris A.
<x xml:space="preserve">Abstract</x> Arterial spin labeling (ASL) is a valuable non‐contrast perfusion MRI technique with numerous clinical applications. Many previous ASL MRI studies have utilized either echo‐planar imaging (EPI) or true fast imaging with steady‐state free precession (true FISP) readouts, which are prone to off‐resonance artifacts on high‐field MRI scanners. We have developed a rapid ASL‐FISP MRI acquisition for high‐field preclinical MRI scanners providing perfusion‐weighted images with little or no artifacts in less than 2 s. In this initial implementation, a flow‐sensitive alternating inversion recovery (FAIR) ASL preparation was combined with a rapid, centrically encoded FISP readout. Validation studies on healthy C57/BL6 mice provided consistent estimation of in vivo mouse brain perfusion at 7 and 9.4 T (249 ± 38 and 241 ± 17 mL/min/100 g, respectively). The utility of this method was further demonstrated in the detection of significant perfusion deficits in a C57/BL6 mouse model of ischemic stroke. Reasonable kidney perfusion estimates were also obtained for a healthy C57/BL6 mouse exhibiting differential perfusion in the renal cortex and medulla. Overall, the ASL‐FISP technique provides a rapid and quantitative in vivo assessment of tissue perfusion for high‐field MRI scanners with minimal image artifacts. Copyright © 2014 John Wiley & Sons, Ltd.